2006
DOI: 10.1101/gad.1428206
|View full text |Cite
|
Sign up to set email alerts
|

Regulon and promoter analysis of theE. coliheat-shock factor, σ32, reveals a multifaceted cellular response to heat stress

Abstract: The heat-shock response (HSR), a universal cellular response to heat, is crucial for cellular adaptation. In Escherichia coli, the HSR is mediated by the alternative factor, 32 . To determine its role, we used genome-wide expression analysis and promoter validation to identify genes directly regulated by 32 and screened ORF overexpression libraries to identify 32 inducers. We triple the number of genes validated to be transcribed by 32 and provide new insights into the cellular role of this response. Our wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
289
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(317 citation statements)
references
References 86 publications
21
289
0
2
Order By: Relevance
“…The measurement of time-course b-galactosidase activity at 37, 42, and 48°C (Fig. S4) indicates that transcription of yrhB seems to be regulated by r 70 -dependent promoter, which also corresponds to the following previous results [18][19][20][21]: the transcription level of yrhB was not increased by the overexpression of rpoH [18,19] and was not upregulated by heat shock [20,21]. Consequently, it seems that YrhB cannot be defined as a traditional heat shock protein.…”
Section: -Dependent Promotersupporting
confidence: 87%
See 1 more Smart Citation
“…The measurement of time-course b-galactosidase activity at 37, 42, and 48°C (Fig. S4) indicates that transcription of yrhB seems to be regulated by r 70 -dependent promoter, which also corresponds to the following previous results [18][19][20][21]: the transcription level of yrhB was not increased by the overexpression of rpoH [18,19] and was not upregulated by heat shock [20,21]. Consequently, it seems that YrhB cannot be defined as a traditional heat shock protein.…”
Section: -Dependent Promotersupporting
confidence: 87%
“…In this study, we also found that YrhB is indispensable for sustaining growth of E. coli BL21(DE3) at high culture temperature. A result of this study and other previous reports [18][19][20][21] show that the transcription of yrhB is not regulated by RpoH, indicating that YrhB cannot be defined as a traditional heat shock protein. This study reports that YrhB is extremely thermostable and keeps monomer conformation under heat shock condition unlike other small heat shock proteins that form multimeric or oligomeric structures.…”
Section: Discussionsupporting
confidence: 51%
“…To assess further how increased cellular levels of m-TyrtRNA Phe affect the global integrity of the proteome, transcript levels of several components of the sigma 32-(rpoH)-and sigma E-(rpoE)-dependent protein stress regulons were measured (Table 1). Consistent with increased levels of misfolded proteins, genes encoding components of the general heat shock response (rpoH, dnaK, and mopA) were up-regulated in the presence of m-Tyr in the PheRS editing-deficient strain (31). In contrast, transcript levels of two components of the sigma E envelope stress response (rpoE and ptr) were unchanged under the conditions studied, but a third Sigma E-dependent transcript, htrA, was 32-fold higher in the editing-deficient strain in the presence of m-Tyr (32).…”
Section: The Integrity Of Protein Synthesis Is Reduced In the Absencementioning
confidence: 86%
“…Multiround in vitro transcription was carried out as reported previously (16), and single-round transcription was done as described (44).…”
Section: Methodsmentioning
confidence: 99%